Effect of prolonged continuous smartphone gaming on upper body postures and fatigue of the neck muscles in school students aged between 10-18 years. Issue 1 (1st January 2021) - Hanphitakphong, Panida; Thawinchai, Nuanlaor; Poomsalood, Somruthai
Abstract: This study investigated the effect of prolonged continuous smartphone gaming on upper body postures and fatigue of the neck muscles in school students. Forty-four students aged between 10 and 18 years were enrolled in this study. All participants were instructed to play an online smartphone game continuously for 20 minutes in a sitting position during dynamic postural analysis. Simultaneously, a wireless surface electromyography (EMG) system was used to collect data from the cervical erector spinae (CES) and upper trapezius (UT) on both sides. The median frequency was considered as an index for muscle fatigue. An inertial measurement unit (IMU) was applied to examine upper body postures kinematics data. The Numeric Rating Scale (NRS-11) was also used to assess self-reported pain intensity in the posterior neck region at pre- and post-game playing. Angles of neck, trunk, left shoulder, and bilateral elbow flexion significantly increased at 10 and 20 minutes (p < 0.05) compared to those at the baseline. Bilateral CES is presented with significantly increased degree of fatigue at 20 minutes (p < 0.05). Neck discomfort significantly increased (p < 0.05) after the completion of the game. These findings revealed that a sustained (20-min) smartphone game playing induced significant awkward posture and resulted in muscle fatigue and discomfort especially in the posterior neck area. It is suggested that prolonged smartphone use should not exceed 10 minutes for students aged 10–18 years with respect to minimizing the biomechanical effects in the neck area. Habitual awkward posture should be carefully noticed during the sustained smartphone use.